Dementia and delirium: recognising common factors. (2nd January 2023) - Dening, Karen Harrison; Moore, Angela
Abstract : Delirium is a multifactorial syndrome that, when superimposed on dementia, can lead to twice the risk of being admitted to acute care than for a person who is cognitively intact. Early detection of delirium can be a challenge, especially when there is an existing diagnosis of dementia. Despite the wealth of literature, there continues to be a widespread lack of knowledge about delirium, and under-detection in all types of health and social care settings. This lack of recognition may lead to poor health outcomes and increased mortality. There is a need for effective training for staff working in community settings, and effective communication between health and social care staff and families who are affected by delirium. Furthermore, delirium superimposed on dementia is common, and may cause distress for patients, caregivers and staff. This article will explore some of the common factors when delirium is comorbid with dementia.